Ibrexafungerp Versus Placebo for Vulvovaginal Candidiasis Treatment: A Phase 3, Randomized, Controlled Superiority Trial (VANISH 303). (1st September 2021) - Schwebke, Jane R; Sobel, Ryan; Gersten, Janet K; Sussman, Steven A; Lederman, Samuel N; Jacobs, Mark A; Chappell, B Todd; Weinstein, David L; Moffett, Alfred H; Azie, Nkechi E; Angulo, David A; Harriott, Itzel A; et al.
Abstract: Background: Current treatment of vulvovaginal candidiasis (VVC) is largely limited to azole therapy. Ibrexafungerp is a first-in-class triterpenoid antifungal with broad-spectrum anti- Candida fungicidal activity. The objective of this study was to evaluate the efficacy and safety of ibrexafungerp compared with placebo in patients with acute VVC. Methods: Patients were randomly assigned 2:1 to receive ibrexafungerp (300 mg twice for 1 day) or placebo. The primary endpoint was the percentage of patients with a clinical cure (complete resolution of vulvovaginal signs and symptoms [VSS] = 0) at test-of-cure (day 11 ± 3). Secondary endpoints included the percentage of patients with mycological eradication, overall success (clinical cure and mycological eradication), clinical improvement (VSS ≤ 1) at test-of-cure, and symptom resolution at follow-up (day 25 ± 4). Results: Patients receiving ibrexafungerp had significantly higher rates of clinical cure (50.5% [95/188] vs 28.6% [28/98]; P = .001), mycological eradication (49.5% [93/188] vs 19.4% [19/98]; P < .001), and overall success (36.0% [64/178] vs 12.6% [12/95]; P < .001) compared with placebo. Symptom resolution was sustained and further increased with ibrexafungerp compared with placebo (59.6% [112/188] vs 44.9% [44/98]; P = .009) at follow-up. Post hoc analysis showed similar rates of clinical cure and clinical improvement at test-of-cure for Black patients (54.8% [40/73] and 63.4% [47/73], respectively) and patients with a body mass index >35 (54.5% [24/44] and 68.2% [30/44], respectively) compared with overall rates. Ibrexafungerp was well tolerated. Adverse events were primarily gastrointestinal and mild in severity. Conclusions: Ibrexafungerp provides a promising safe and efficacious oral treatment that mechanistically differs from current azole treatment options for acute VVC. Abstract : Ibrexafungerp was statistically superior to placebo in reduction of signs and symptoms of acute vulvovaginal candidiasis regardless of the endpoint assessed. This advantage was maintained across subpopulations including African American patients or patients with a body mass index >35.